Quick Training on Answering Mathematics National Examination for Algebraic Forms in Junior High School Kartika 1-4 - Sirait, Debora (Talenta Publisher, 2021)
The National Examination, usually abbreviated as UN, is a system of evaluating the national primary and secondary education standards as well as the equality of education quality between regions carried out by the Education Assessment Center. Algebra is a part of a large field of mathematics, together with number theory, geometry and analysis. In its most common form, algebra is the study of mathematical symbols and their rules. The method used in interactive learning was chosen to deliver appropriate training which was carried out in three stages, namely the field exploration stage, the implementation stage, and the evaluation stage. With this method, it is hoped that teachers and students can see quick tricks on solving the National Mathematics Examination questions.